A Ferrite Synaptic Transistor with Topotactic Transformation. Issue 19 (29th March 2019) - Ge, Chen; Liu, Chang‐xiang; Zhou, Qing‐li; Zhang, Qing‐hua; Du, Jian‐yu; Li, Jian‐kun; Wang, Can; Gu, Lin; Yang, Guo‐zhen; Jin, Kui‐juan
Abstract: Hardware implementation of artificial synaptic devices that emulate the functions of biological synapses is inspired by the biological neuromorphic system and has drawn considerable interest. Here, a three‐terminal ferrite synaptic device based on a topotactic phase transition between crystalline phases is presented. The electrolyte‐gating‐controlled topotactic phase transformation between brownmillerite SrFeO2.5 and perovskite SrFeO3− δ is confirmed from the examination of the crystal and electronic structure. A synaptic transistor with electrolyte‐gated ferrite films by harnessing gate‐controllable multilevel conduction states, which originate from many distinct oxygen‐deficient perovskite structures of SrFeO x induced by topotactic phase transformation, is successfully constructed. This three‐terminal artificial synapse can mimic important synaptic functions, such as synaptic plasticity and spike‐timing‐dependent plasticity. Simulations of a neural network consisting of ferrite synaptic transistors indicate that the system offers high classification accuracy. These results provide insight into the potential application of advanced topotactic phase transformation materials for designing artificial synapses with high performance. Abstract : A ferrite synaptic transistor with topotactic transformation is presented. The electrolyte‐gating‐controlled topotactic phase transformation between the brownmillerite SrFeO2.5 and perovskite SrFeO3− δ is confirmed by the crystal and electronic structure measurements. This ferrite synaptic transistor can mimic important synaptic functions such as synaptic plasticity and spike‐timing‐dependent plasticity.